Evaluation of a Strain Sweep Tests Protocol as a Tool for Assessing the Homogeneity of SBR Copolymer Composition - Corrêa, Harrison Lourenço; Guimarães Furtado, Cristina Russi (Journal of Research Updates in Polymer Science, 2024)
Global competition in products and services demands constant improvement in production systems. Similarly, it is essential for industries to have quality control tools capable of assessing the compliance of a given product at a lower cost and with greater effectiveness. In the rubber and composite industry, where complex formulation and mixing systems can affect not only the quality of the final product but also the processing of rubber, the development of a protocol that assumes this function is important. The present study developed samples of elastomeric blends based on styrene-butadiene copolymer (SBR) with different filler concentrations (30, 60, and 90 phr of ground tire rubber as filler), which were analyzed using an oscillating cavity rheometer (MDpt-TechPro). Based on a proprietary testing protocol, the degree of homogeneity of the composites was evaluated, which was compared with scanning electron microscopy studies. The implemented protocol, which provides results within 30 minutes, proved to be promising for quality control of these blends, and it can be used by rubber processing industries, saving both time and cost, being an unprecedented study on the ’homogeneity-rheology’ relationship.